The living dead? Perception of persons in the unresponsive wakefulness syndrome in Germany compared to the USA - Inga Steppacher; Johanna Kissler (BMC Psychology, 2018)
Abstract Background The extent to which people ascribe mind to others has been shown to predict the extent to which human rights are conferred. Therefore, in the context of disorders of consciousness (DOC), mind ascription can influence end of life decisions. A previous US-American study indicated that participants ascribed even less mind to patients with unresponsive-wakefulness-syndrome (UWS) than to the dead. Results were explained in terms of implicit dualism and religious beliefs, as highly religious people ascribed least mind to UWS. Here, we addresses mind ascription to UWS patients in Germany. Methods We investigate the perception of UWS patients in a large German sample (N = 910) and compare the results to the previous US data, addressing possible cultural differences. We further assess effects of medical expertise, age, gender, socio-economic status and subjective knowledge about UWS in the German sample. Results Unlike the US sample, German participants did not perceive UWS patients as “more dead than dead”, ascribing either equal (on 3 of 5 items) or more (on 2 items) mental abilities to UWS patients than to the dead. Likewise, an effect of implicit dualism was not replicated and German medically trained participants ascribed more capabilities to UWS patients than did a non-medical sample. Within the German sample, age, gender, religiosity and socio-economic status explained about 15% of the variability of mind ascription. Age and religiosity were individually significant predictors, younger and more religious people ascribing more mind. Gender had no effect. Conclusion Results are consistent with cross-cultural differences in the perception of UWS between Germany and the USA, Germans ascribing more mind to UWS patients. The German sample ascribed as much or more but not less mind to a UWS patient than to a deceased, although within group variance was large, calling for further research. Mind ascription is vital, because, in times of declining resources for healthcare systems, and an increasing legalization of euthanasia, public opinion will influence UWS patients’ rights and whether ‘the right to die’ will be the only right conceded to them.